Editorial Board Members' Collection Series: Advanced Oxidation Processes of Organic Contaminants (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Organic pollutants are increasingly recognized as a critical threat to both ecosystems and human health. Amidst the growing demand for environmental measures, such as sustainable development goals and carbon neutrality, the need for highly efficient wastewater treatment technologies has never been more critical. This Reprint compiles studies on advanced oxidation processes (AOPs) for the removal of organic pollutants, including ozone combined with biological oxidation, photocatalysis, peroxymonosulfate (PMS) activation, and discharge plasma. Contributing authors Yu Li, Zijian Zhang, Xiaoping Wang, Jingyu Sun, and Zongli Huo have developed novel PMS activators to enhance the degradation efficiency of antibiotics and antioxidants, as well as to analyze and detect the toxicity of transformation products. Isaac Chairez has integrated ozone with biodegradation technology for the treatment of paper mill wastewater. Se Wang has employed DFT/TDDFT calculation methods to elucidate the direct and indirect photolysis of pollutants. He Guo and Xian Cheng have utilized plasma coupling technology to treat dye and emergency wastewater. This Reprint provides foundational data for the research and development of wastewater treatment technologies, offering relevant researchers access to cutting-edge advancements and inspirational research in the field of organic pollutants.